Bates guide to physical examination and history taking / Lynn S. Bickley, Peter G. Szilagyi, Richard M. Hoffman ; guest editor, Rainier P. Soriano. - Bickley, Lynn S.
The thirteenth edition of Bates' Guide to Physical Examination and History Taking is your comprehensive guide to learning to effectively conduct the health interview and physical examination. This section introduces you to the features and learning tools that will lead to successful health assessments, regional examinations, and working with special patient populations. At the start of every chapter, you will see a list of additional learning resources that complement the book in order to build your knowledge and confidence in history taking and examination. The Bates' Visual Guide to Physical Examination offers over more than 8 hours of video content and delivers head-to-toe and systems-based physical examination techniques. When used alongside the book, you have a complete learning solution for preparedness for the boards and patient encounters